2019
DOI: 10.1038/s41598-019-41869-9
|View full text |Cite
|
Sign up to set email alerts
|

The clinical features and prognosis of 100 AIDS-related lymphoma cases

Abstract: To improve outcomes and risk assessment, we systematically analyzed the clinical features of patients with acquired immunodeficiency syndrome (AIDS)-related lymphoma (ARL) and identified survival-associated factors. Data were collected from 100 patients diagnosed with ARL at the Henan Provincial Infectious Disease Hospital in China. The progression-free survival (PFS) duration and 2-year overall survival (OS) rate were determined. A multivariate analysis was used to evaluate the associations between survival a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 29 publications
3
22
0
2
Order By: Relevance
“…However, indisputably, it is well known that HIV infection is also, a risk factor for several B-cell and non-AIDS malignances, including Hodgkin and non-Hodgkin lymphoma [36, 37, 46, 47]. It should also be pointed out that HIV-associated lymphoma compared to lymphoma in HIV-negative patients is characterized by advanced diseases occurring more often, extranodal involvement, and being usually associated with Epstein-Barr virus [16]. A few studies have shown that biomarkers for aberrant B-cell activation are elevated in HIV-positive patients who develop lymphomas.…”
Section: Hivmentioning
confidence: 99%
See 1 more Smart Citation
“…However, indisputably, it is well known that HIV infection is also, a risk factor for several B-cell and non-AIDS malignances, including Hodgkin and non-Hodgkin lymphoma [36, 37, 46, 47]. It should also be pointed out that HIV-associated lymphoma compared to lymphoma in HIV-negative patients is characterized by advanced diseases occurring more often, extranodal involvement, and being usually associated with Epstein-Barr virus [16]. A few studies have shown that biomarkers for aberrant B-cell activation are elevated in HIV-positive patients who develop lymphomas.…”
Section: Hivmentioning
confidence: 99%
“…Moreover, there are some studies suggesting that the MS incidence in HIV-positive patients is lower than that in general population because immunodeficiency induced by this virus may prevent development of MS [12–15]. However, in HIV, the risk of malignancy is significantly increased and more than 40% of HIV-infected people are eventually diagnosed with HIV- or acquired immunodeficiency syndrome- (AIDS-) related lymphoma (ARL) [16].…”
Section: Introductionmentioning
confidence: 99%
“…The subtypes of the ARL were 33 DLBCL (47.1%), 15 plasmablastic lymphoma (PBL) (21.4%), 12 Hodgkin's lymphoma (HL) (17.1%), 3 Burkitt's lymphoma (BL) (4.3%), 2 high grade B-cell lymphoma (2.9%), 2 follicular lymphoma (FL) (2.9%), 1 PCNSL (1.4%), 1 primary effusion lymphoma (PEL) (1.4%), and 1 peripheral T cell lymphoma (PTCL) (1.4%) (8). Several other studies have shown that the most common subtypes of the ARL is the DLBCL, followed by BL (9)(10)(11)(12)(13)(14). Multiple factors have been shown to influence the pathogenesis of HIV-associated lymphoma.…”
Section: Epidemiologymentioning
confidence: 99%
“…Múltiples factores relacionados con el paciente o su patología son contribuyentes al pronóstico, y por lo tanto, a la supervivencia de este, siendo los niveles de CD4 el factor predictor más significa-tivo en estos individuos (tabla 3). Según un estudio llevado a cabo en 100 pacientes en el Hospital Provincial de Enfermedades Infecciosas de Henan en China, factores como una edad menor de 45 años, niveles de CD4 <100 células/mm 3 , un Índice Pronóstico Internacional (IPI) alto y un nivel elevado de LDH, son los predictores de peor pronóstico para un paciente positivo para VIH con enfermedad linfoproliferativa concomitante [37].…”
Section: Pronósticounclassified